On the advantages and disadvantages of virtual continuing medical education: a scoping review (Canadian Medical Education Journal, 2023)
Introduction: With the COVID-19 pandemic, most continuing medical education activities became virtual (VCME). The authors conducted a scoping review to synthesize the advantages and disadvantages of VCME to establish the impact of this approach on inequities that physicians face along the intersections of gender, race, and location of practice.Methods: Guided by the methodological framework of Arksey and O’Malley, the search included six databases and was limited to studies published between January 1991 to April 2021. Eligible studies included those related to accredited/non-accredited post-certification medical education, conferences, or meetings in a virtual setting focused on physicians. Numeric and inductive thematic analyses were performed.  Results: 282 studies were included in the review. Salient advantages identified were convenience, favourable learning formats, collaboration opportunities, effectiveness at improving knowledge and clinical practices, and cost-effectiveness. Prominent disadvantages included technological barriers, poor design, cost, lack of sufficient technological skill, and time. Analysis of the studies showed that VCME was most common in the general/family practice specialty, in suburban settings, and held by countries in the Global North. A minority of studies reported on gender (35%) and race (4%). Discussion: Most studies report advantages of VCME, but disadvantages and barriers exist that are contextual to the location of practice and medical subspecialty. VCME events are largely organized by Global North countries with suboptimized accessibility for Global South attendees. A lack of reported data on gender and race reveals a limited understanding of how VCME affects vulnerable populations, prompting potential future considerations as it evolves.